Untying the Photophysics of Quinolinium‐Based Molecular Knots and Links. Issue 7 (8th January 2020) - Caprice, Kenji; Aster, Alexander; Cougnon, Fabien B. L.; Kumpulainen, Tatu
Abstract: Complex molecular knots and links are still difficult to synthesize and the properties arising from their topology are mostly unknown. Here, we report on a comparative photophysical study carried out on a family of closely related quinolinium‐based knots and links to determine the impact exerted by topology on the molecular backbone. Our results indicate that topology has a negligible influence on the behavior of loosely braided molecules, which mostly behave like their unbraided equivalents. On the other hand, tightly braided molecules display distinct features. Their higher packing density results in a pronounced ability to resist deformation, a significant reduction in the solvent‐accessible surface area and favors close‐range π–π interactions between the quinolinium units and neighboring aromatics. Finally, the sharp alteration in behavior between loosely and tightly braided molecules sheds light on the factors contributing to braiding tightness. Abstract : Untying the knot : The topology of a molecule affects its physical and chemical properties in many ways. The built‐in quinolinium chromophore in a family of structurally related knots and links, exhibits sharp alteration in its properties depending on the braiding tightness as uncovered by UV/Vis, transient absorption and NMR spectroscopies.